2013
DOI: 10.4103/0972-9941.110963
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy in complicated appendicitis: Is it safe?

Abstract: BACKGROUND:Because of lack of good evidence supporting laparoscopic approach for complicated appendicitis, we carried out this study to evaluate efficacy of laparoscopic appendectomy (LA) in management of patients with complicated appendicitis.MATERIALS AND METHODS:This study was carried out in Surgical Department, Minia University, Egypt involving 214 patients underwent appendectomy for complicated appendicitis over three years. 132 patients underwent LA and remaining 82 patients underwent OA. Parameters stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
(46 reference statements)
7
25
1
Order By: Relevance
“…This may be due to the need for peritoneal lavage and the need for a tying of base in the laparoscopic procedure (17)(18)(19)(20)(21)(22).Despite this finding, to the detriment of the laparoscopic method, the median length of hospitalization (85.2 hours vs. 98.6 hours) and the mean severity of postoperative pain (6.3 vs. 7.2) were significantly shorter compared to open surgery. We found that the results of a study done by Mohamed and Mahran (2013), on 133 patients with complicated acute appendicitis in the laparoscopic surgery group and 82 patients with complicated acute appendicitis in the open surgery group are correlate with the findings of our study that postoperative analgesia and the average duration of hospitalization after surgery in the open surgery group is significantly more (5). In another study by Garg et al (2009) on patients with complicated acute appendicitis who go under open surgery (61 patients) or laparoscopic surgery (49 patients) the postoperative pain severity and average hospitalization (3 day 6 versus day 1) was significantly higher in the first group (23).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This may be due to the need for peritoneal lavage and the need for a tying of base in the laparoscopic procedure (17)(18)(19)(20)(21)(22).Despite this finding, to the detriment of the laparoscopic method, the median length of hospitalization (85.2 hours vs. 98.6 hours) and the mean severity of postoperative pain (6.3 vs. 7.2) were significantly shorter compared to open surgery. We found that the results of a study done by Mohamed and Mahran (2013), on 133 patients with complicated acute appendicitis in the laparoscopic surgery group and 82 patients with complicated acute appendicitis in the open surgery group are correlate with the findings of our study that postoperative analgesia and the average duration of hospitalization after surgery in the open surgery group is significantly more (5). In another study by Garg et al (2009) on patients with complicated acute appendicitis who go under open surgery (61 patients) or laparoscopic surgery (49 patients) the postoperative pain severity and average hospitalization (3 day 6 versus day 1) was significantly higher in the first group (23).…”
Section: Discussionsupporting
confidence: 87%
“…The mean duration of hospitalization in the laparoscopic appendectomy group was 85.2 ±11.4 hours (60-110) and in the open appendectomy group was 98.6 ±18.1 hours (60-168) (p <0.001). Mean pain score in laparoscopic appendectomy group was 6.3±1.7 (3)(4)(5)(6)(7)(8)(9) and in open appendectomy group was 7.2±1.6 (3-9) (p <0.001).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Perforated appendicitis in childhood occurs mostly due to the delays in hospital admission and improper management of abdominal pain. Open surgery is a well-accepted procedure for the management of appendicitis [8]. However, with the increased experience of the surgeons on minimally invasive techniques, appendectomy can be performed laparoscopically in perforated appendicitis cases as well [9].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional multiport laparoscopic appendectomy (CMLA) has gained broad acceptance among general surgeons because of several advantages, such as smaller incision, reduced postoperative pain, less wound infection, more rapid recovery and better cosmetic result when compared with open appendectomy (OA), for both uncomplicated and complicated appendicitis, across the most illness severity groups [1,2,3]. Therefore, CMLA is recommended as the preferred technique for acute appendicitis.…”
Section: Introductionmentioning
confidence: 99%